2015
DOI: 10.1007/s11676-015-0060-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial activity and nutrients of evergreen broad-leaf forests in mid-subtropical region of China

Abstract: To better understand the effects of forest succession on soil microbial activity, a comparison of soil microbial properties and nutrients was conducted between three forest types representing a natural forest succession chronosequence. The study compared a pine (Pinus massoniana) forest (P F ), a pine and broadleaf mixed forest (M F ) and an evergreen broadleaf forest (B F ), in the Yingzuijie Biosphere Reserve, Hunan Province, China. Results showed that soil nutrients in the M F and B F plots were higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…In this study, the highest soil MBC content was found in CBMF. This result agreed with the conclusion of Zeng et al (2015). The MBC content correlated positively with the SOC content (Figure 6), which is considered as a labile organic carbon pool (Liang et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
“…In this study, the highest soil MBC content was found in CBMF. This result agreed with the conclusion of Zeng et al (2015). The MBC content correlated positively with the SOC content (Figure 6), which is considered as a labile organic carbon pool (Liang et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
“…q CO 2 refers to the ratio between the soil BR and MBC [ 34 ]. This parameter not only represents the size and activity of microbial biomass, but also indicates the maturity of the soil ecosystem [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…q CO 2 organically links the size of the microbial biomass with the biological activity and function of the microbial community [ 32 , 34 ]. This parameter can reveal the physiological characteristics of a microbial community [ 21 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations